2012
DOI: 10.1002/ajpa.22114
|View full text |Cite
|
Sign up to set email alerts
|

Salivary concentration of progesterone and cortisol significantly differs across individuals after correcting for blood hormone values

Abstract: Between‐individual variation of salivary progesterone (P4) and cortisol levels does not always closely reflect blood hormone concentrations. This may be partly a function of individual differences in salivary hormone excretion. We tested whether time of day at sampling and ethnicity contributed to individual variation in salivary hormones after adjusting for blood hormone levels. Forty‐three Caucasian and 15 Japanese women (18–34 years) collected four sets of matched dried blood spot (DBS) and saliva specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
(84 reference statements)
1
25
0
Order By: Relevance
“…We found a strong positive correlation between salivary and serum cortisol in the morning, which is in agreement with other studies (11). The study verified the earlier notion that morning saliva cortisol can be high, but does not have to be, in children with recurrent abdominal pain of psychosomatic origin.…”
Section: Discussionsupporting
confidence: 93%
“…We found a strong positive correlation between salivary and serum cortisol in the morning, which is in agreement with other studies (11). The study verified the earlier notion that morning saliva cortisol can be high, but does not have to be, in children with recurrent abdominal pain of psychosomatic origin.…”
Section: Discussionsupporting
confidence: 93%
“…Little information is available on the relationship between cortisol and metabolic indicators in normal weight population samples. However, recent work has shown that there are systematic salivary cortisol differences relative to blood secretion in a sample of normal weight individuals (Konishi et al, ), raising the question of whether these systematic individual differences in cortisol secretion are associated with variation in metabolic biomarkers.…”
mentioning
confidence: 99%
“…Using four matched specimen sets of blood and saliva, Konishi et al () found systematic individual differences in salivary hormone concentration relative to blood hormone concentration, for two different but related hormones, cortisol and progesterone. After correcting for blood hormone values, individuals who were high salivary secretors for one hormone were also high salivary secretors for the other hormone, and the same concordance was observed for medium and low salivary secretors.…”
mentioning
confidence: 99%
See 2 more Smart Citations